(untitled) (Ictus, 2022)
The quality of stroke care begins with the standardization of hospital processes. We present a visually accessible resource for the complex-care process of acute ischemic stroke. The purpose of this tool is to facilitate decision-making in the management of acute ischemic stroke in any emergency room and to generate a significant impact on the quality of care, reducing median delay times and promoting efficiency and safety in each of its steps.